Injectable Antibiotics Market in Lower Extremity Infections : A Target Marketing Perspective - Purkayastha, Sandipon; Deb, Sunanda; Chakravorty, Shibashish (Indian Journal of Marketing, 2017)
With the emergence of more and more local pharmaceutical companies in India, brand-launch has become extremely predicable, given that the pattern suggests one that follows suit. Many local companies are often found to be impetuous in launching their own brands of a molecule that commands a luring market size and is on its growth trajectory. The huge number of oral Rabeprazole and Vitamin D3 brands can be cited as two of the many molecules in the market today, standing as testimonies to the fact. Today, we have 484 and 648 brands of Rabiprazole and Vitamin D3 brands, respectively in the market as updated in medindia.net [Med India(2016a) and Med India (2016b)]. Such typical ideas towards executing new brand-registrations and their subsequent market-launch has left its heavy toll on companies' marketing team for the dearth of any brand differentiation. Das (2010) observed that there is an enormous gap between those companies that claim to be customer-focused and those which actually are. Hence, not much value creation - either for the doctors or their patients - is made possible by most companies. With a view to create value for the doctors, we conducted this study by focusing upon one clinical-challenge area (i.e. lower extremity infections) to recognize the clinical needs around that and ascertain if a new injectable antibiotic launch with a targeted promotion in the indication would create a lucrative niche for a marketing company. Based on our findings, we concluded that â€œneed based target marketingâ€ may well turn out as the game changer for pharmaceutical companies. The most significant outcome of our study was the recognition of the possible lucrative niche market for injectable antibiotics that is presented by hospitalized patients with lower extremity infections (LEIs) .